2015
DOI: 10.1002/adsc.201500263
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Self‐Sufficient Arene Reduction to Cyclohexane Derivatives Using a Combination of Platinum on Carbon and 2‐Propanol

Abstract: Va riousa renesh ave been hydrogenated using platinum on carbon in a2 -propanol-aqueous mixed solvent at 100 8 8Cw ithout the addition of flammable hydrogen gas to givet he corresponding cyclohexane derivatives.2 -Propanol plays ar ole as an efficient hydrogen source based on the platinum on carbon-catalyzed dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The present dehydrogenation method for secondary alcohols could be applied as an in situ hydrogen‐generation method. The hydrogen generated by platinum metal on carbon catalyzed dehydrogenation of isopropanol ( i ‐PrOH) as a hydrogen carrier was utilized as an activator of the platinum metal or reductant to accomplish the reduction and deuteration …”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…The present dehydrogenation method for secondary alcohols could be applied as an in situ hydrogen‐generation method. The hydrogen generated by platinum metal on carbon catalyzed dehydrogenation of isopropanol ( i ‐PrOH) as a hydrogen carrier was utilized as an activator of the platinum metal or reductant to accomplish the reduction and deuteration …”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…Deuterium (D)-labeled compounds are utilized in a wide variety of scientific fields, such as mechanistic investigations of organic reactions, tracers in microanalyses, elucidation of drug metabolism, heavy drugs, quantitative mass spectrometry analyses, etc., because of the specific property of the D atom as a stable isotope of the H atom and the isotope effect, such as the higher bond dissociation energy of the C–D bond in comparison with the corresponding C–H bond. The H–D exchange reaction is a straightforward methodology within various synthetic methods. , We have continuously developed the platinum group metal-catalyzed H–D exchange reactions of various organic compounds based on activation of the catalyst metal using hydrogen gas (H 2 ). , Among them, benzoic acid ( 1a ) was less reactive, and comparatively harsh reaction conditions were required to achieve excellent D contents on its aromatic nucleus (Scheme , eqs 1 and 2). H 2 is a key activator of Pt metal supported on carbon, and the Pt/C-catalyzed deuteration of 1a could efficiently proceed in D 2 O under H 2 at atmospheric pressure at 180 °C (Scheme , eq 1) .…”
Section: Introductionmentioning
confidence: 99%
“…Platinum group metals on carbon, such as Pt/C, can catalyze the dehydrogenation of secondary alcohols to ketones accompanied by the generation of H 2 . Therefore, H 2 generated in situ via the Pt/C-catalyzed dehydrogenation of 2-propanol (isopropanol, i -PrOH) as a secondary alcohol was also utilized as an activator of Pt metal to produce deuterium-labeled benzoic acid ( 1a - d 5 ) in a mixed solvent [ i -PrOH/ c -hexane ( c -Hex)/D 2 O] at 100 °C (Scheme , eq 2)…”
Section: Introductionmentioning
confidence: 99%
“…6 We have continuously developed methods of heterogeneously catalyzed dehydrogenation of organic substrates (e.g., alcohols 7 and cyclohexane derivatives 8 ) and investigated ways of mechanochemical H 2 generation from water, 9a,9b alkanes, 9c and ether 9c to avoid CO 2 emission. Furthermore, we demonstrated that in situ generated H 2 can be directly utilized for reduction, 9,10 as exemplified by Pt on carbon (Pt/C)-catalyzed arene reduction in 2-propanol (2-PrOH) as a solvent and hydrogen source (Scheme 1, A). 10b Unexpectedly, although this reduction proceeded smoothly in a sealed stainless steel tube, it could not be realized in a sealed glass tube.…”
Section: Introductionmentioning
confidence: 99%